2012
DOI: 10.1155/2012/549850
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Some Phytochemicals from Indian Traditional Plants

Abstract: The present study was designed to evaluate relative contribution of different polyphenols (total phenolics, flavonoids, flavonols) and their antioxidants activities in aqueous extracts of different parts of some plants; Argemone mexicana, Datura metel, Calotropis procera, Thevetia peruviana, and Cannabis sativa. The antioxidants (total phenolics, flavonoids, flavones) were determined by chemical methods. The antioxidant capacities of these extracts were evaluated by FRAP assay. The results demonstrated that ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 42 publications
(42 reference statements)
0
25
1
Order By: Relevance
“…Saponin has been reported to have antifungal capacities (Sparg et al, 2004). Also, the amount of phenolic and flavonoids content on aqueous extracts of D. metel aerial parts was determined by Srivastava et al (2012). The results showed that the maximum phenolic content was present in flower (19.75 mg/g) and the highest flavonoids content was found in leaves (2 mg/g).…”
Section: Discussionmentioning
confidence: 99%
“…Saponin has been reported to have antifungal capacities (Sparg et al, 2004). Also, the amount of phenolic and flavonoids content on aqueous extracts of D. metel aerial parts was determined by Srivastava et al (2012). The results showed that the maximum phenolic content was present in flower (19.75 mg/g) and the highest flavonoids content was found in leaves (2 mg/g).…”
Section: Discussionmentioning
confidence: 99%
“…In plants, they are essential pigments and are found in flowers, leaves and stems giving them the typical color but add also to the smell and flavor of a particular Cannabis strain. Flowers of hemp rank among the plants with the highest flavonoid content and antioxidant power; the total content in the Cannabis leaves and flowers can reach 2.5% of its dry weight (green tea, for comparison: 0.5% -1.5%); [45,46]. In an epidemiologic study, the daily intake of 25.9 mg flavonoids (quercetin, kaempferol, myricetin, apigenin and luteolin) was related to a significant decrease of cancer symptoms [47].…”
Section: Hemp (Cannabis) Contains Also Flavonoidsmentioning
confidence: 99%
“…Total flavonols in each extract was determined using the method of Srivastava et al, 21 Briefly, 1.0 mL of 2% AlCl3 in methanol and 1.5 mL of 5% sodium acetate solutions were added to 12.5 µl of each extract (5 mg/mL in methanol) solution. Each mixture was incubated in water bath at 37˚C for 30 min and absorbance taken at 440 nm.…”
Section: Determination Of Flavonolsmentioning
confidence: 99%